Antagonistic interaction between Wnt and Notch activity modulates the regenerative capacity of a zebrafish fibrotic liver model. Issue 5 (10th September 2014) - Huang, Mianbo; Chang, Angela; Choi, Minna; Zhou, David; Anania, Frank A.; Shin, Chong Hyun
<x xml:space="preserve">Abstract</x> In chronic liver failure patients with sustained fibrosis, excessive accumulation of extracellular matrix proteins substantially dampens the regenerative capacity of the hepatocytes, resulting in poor prognosis and high mortality. Currently, the mechanisms and the strategies of inducing endogenous cellular sources such as hepatic progenitor cells (HPCs) to regenerate hepatocytes in various contexts of fibrogenic stimuli remain elusive. Here we aim to understand the molecular and cellular mechanisms that mediate the effects of sustained fibrosis on hepatocyte regeneration using the zebrafish as a model. In the ethanol‐induced fibrotic zebrafish model, we identified a subset of HPCs, responsive to Notch signaling, that retains its capacity to regenerate as hepatocytes. Discrete levels of Notch signaling modulate distinct cellular outcomes of these Notch‐responsive HPCs in hepatocyte regeneration. Lower levels of Notch signaling promote amplification and subsequent differentiation of these cells into hepatocytes, while high levels of Notch signaling suppress these processes. To identify small molecules facilitating hepatocyte regeneration in the fibrotic liver, we performed chemical screens and identified a number of Wnt agonists and Notch antagonists. Further analyses demonstrated that these Wnt agonists are capable of attenuating Notch signaling by inducing Numb, a membrane‐associated protein that inhibits Notch signaling. This suggests that the antagonistic interplay between Wnt and Notch signaling crucially affects hepatocyte regeneration in the fibrotic liver. Conclusion: Our findings not only elucidate how signaling pathways and cell‐cell communications direct the cellular response of HPCs to fibrogenic stimuli, but also identify novel potential therapeutic strategies for chronic liver disease. (Hepatology 2014;60:1753–1766)